ANÁLISIS MINERALÓGICO CUALITATIVO Y CUANTITATIVO EN ARCILLAS POR DIFRACCIÓN DE RAYOS X Y EL MÉTODO RIETVELD USANDO EL PROGRAMA FULLPROF - Quille R., Rubén (2006)
In the present work were making the qualitative and quantitative identification of the main mineralogical phases present in a specimen of clay, to show a method to adjust their crystalline structures and at the same time determine the concentrations of the mineralogical phases present in the specimen of clay. The data were obtained with an Universal Difractómeter and the Hanawalt method was applied for the identification of the phases, for it we use the softwares DRXWIN 2.2 and CreaFit 2.2. The Rietveld refinement were making using the FullProf program, it allowed refine the net parameters, atomic positions and it determine concentrations of the mineralogical phases present in the specimen, at the same time it allows represent graphically refine crystalline structure of each mineralogical phase and the Fourier Map.